Co-precipitation method for the preparation of fine ferroelectric BaBi2M2O9 - Gaikwad, S. P.; Potdar, HS; Samuel, V; Ravi, V (Ceramics International, 2005)
A simple co-precipitation technique had been successfully applied for the preparation of pure fine powders of single phase BaBi2Nb2O9. Ammonium hydroxide and ammonium oxalate were used to precipitate Ba2+, Bi3+ and Nb5+ cations simultaneously. No pyrochlore phase was formed while heating powder at 800 degrees C and pure BaBi2Nb2O9 phase was found to be formed by X-ray diffraction (XRD). Particle size and morphology was studied by transmission electron spectroscopy (TEM). The room temperature dielectric constant at 1 kHz is 100. The ferroelectric hysteresis loop parameters of these samples were also studied. (c) 2004 Elsevier Ltd and Techna Group S.r.l. All rights reserved.
Keywords: dielectric properties; Electron microscopy; ferroelectric properties; powders chemical preparation